Pengembangan Media Pembelajaran Pop-Up Book Keberagaman Budaya Indonesia Pada Pelajaran IPAS Untuk Siswa Kelas 4 Sekolah Dasar - Julianti, Diah; Yurdayanti; Iqbal Arrosyad, Muhammad (JBES (Journal Basic Education Skills), 2024)
This research was motivated by the problem that the learning process on Indonesian Cultural Diversity material revealed a lack of media used by teachers; no additional media is used in the learning process, so that students do not show effectiveness in following the learning process; As a result, students' interest is very low and they feel bored in class. The aim of this research is to provide credible and useful pop-up book learning materials for science classes and science learning for Indonesian cultural diversity in grade 4 elementary school students. Analysis, design, development, implementation and evaluation are the five steps of the ADDIE paradigm which are used in the form of studies known as research and development (R&D). The quantitative descriptive data analysis method used in the data analysis approach involves three validators, media experts, material experts and language experts who carry out data validity. Practicality data was collected from instructor answers and student questionnaire findings. This learning tool uses a questionnaire. Media experts got a score of 92.3%, material experts got a score of 87%, and language experts got a score of 85% in the validator assessment; as a consequence, they were approved and placed in the very valid category. Teacher reactions to the media were 88%, while large-scale test results were 93.3% and small-scale test results were 92%. It was determined that the use of pop-up books as a means of teaching science and scientific teaching related to the diversity of Indonesian culture for fourth grade elementary school children was very effective and useful.